2015
DOI: 10.1007/s12035-015-9422-9
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone-Induced Differentiation of Astrocytes is Associated with Transcriptional Upregulation of β-arrestin-1 and β-adrenergic Receptor-Mediated Endosomal Signaling

Abstract: Thyroid hormones (TH) promote differentiation of astrocytes. We have previously reported that a downstream role β-adrenergic receptor (β-AR) system in such effects of TH. Although evidences indicate strong interaction between TH and the β-ARs, the underlying mechanism is poorly understood. In the present study, we further explored the influence of TH on β-AR signaling during the differentiation process. Unlike β1-AR, binding of (125)I-pindolol to β2-AR in cell membranes was significantly decreased at 2 h of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Li et al, 2002). Moreover, another study showed that ARRB2 plays a critical role in the differentiation of astrocytes induced by TH (Das et al, 2016). In our study, we verified that T3 upregulated the transcription of both ARRBs and increased ARRB2 protein expression in cardiomyocytes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Li et al, 2002). Moreover, another study showed that ARRB2 plays a critical role in the differentiation of astrocytes induced by TH (Das et al, 2016). In our study, we verified that T3 upregulated the transcription of both ARRBs and increased ARRB2 protein expression in cardiomyocytes.…”
Section: Discussionsupporting
confidence: 82%
“…They showed the regulation of visual arrestins by retinoic acid (nuclear receptors of TH and retinoic acid are usually found as heterodimers in the nucleus to regulate gene transcription; Li et al, 2002). Moreover, another study showed that ARRB2 plays a critical role in the differentiation of astrocytes induced by TH (Das et al, 2016). In our study, we verified that T3 upregulated the transcription of both ARRBs and increased ARRB2 protein expression in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…b-arrestin1 (barr1) is a ubiquitous multifunctional adaptor protein that acts as a scaffold and adaptor to regulate cell proliferation, apoptosis, and differentiation (12)(13)(14). Our previous research has shown that barr1 has a close relationship with ER stress pathways and that barr1 inhibited ER stress and the PUMA pathway via restriction of the induced nitric oxide synthase (iNOS)/phosphorylated P65 (p-P65) axis, reducing gastric mucosa apoptosis in portal hypertension gastropathy (15).…”
mentioning
confidence: 99%
“…Beta-arrestin1 (ARRB1), belonging to the arrestin family of proteins, was originally identified as an adaptor protein that regulates G protein-coupled receptor (GPCR) desensitization and internalization (Kang et al, 2005). ARRB1 is now known to be a ubiquitous adaptor protein that plays a role in the regulation of cell proliferation, differentiation, autophagy, and apoptosis (Yang et al, 2015;Das et al, 2016;Zhan et al, 2016;Lei et al, 2021). In addition to cytoplasmic functions, the nuclear activity of ARRB1 has recently been reported (Hoeppner et al, 2012;Purayil et al, 2015) and is thought to be a nuclear transcriptional regulator of the endothelin-1-induced β-catenin signaling (Rosanò et al, 2013).…”
Section: Introductionmentioning
confidence: 99%